2014
DOI: 10.1021/jp500954v
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Density of States of Strongly H-Bonded Interfacial Water: Insights from Inelastic Neutron Scattering and Theory

Abstract: The molecular scale interaction between water and an oxide surface depends on the strength of the surface hydrogen bonds (Hbonds) through a subtle interplay among surface structure, surface atom polarity, and orientation of sorbed species. Tin oxide (SnO 2 ) in the rutile structure is an important catalytic and gas-sensing material, and its surface properties have been the subject of intense scrutiny. Here we show that the vibrational dynamics of H 2 O and OH sorbed on SnO 2 nanoparticles, probed with inelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 54 publications
6
55
0
1
Order By: Relevance
“…In fact, high-pressure crystalline and amorphous phases of ice show significant differences in the intramolecular vibration range compared to Ih ice 149,150 . The blue shift of the O-H stretching mode of water interacting with biomolecule 159 or oxide 160 surface, or confined within carbon nanotubes 161 is consistent with the weakening of the hydrogen-bonded water network in these systems.…”
Section: Intramolecular Vibrationssupporting
confidence: 60%
“…In fact, high-pressure crystalline and amorphous phases of ice show significant differences in the intramolecular vibration range compared to Ih ice 149,150 . The blue shift of the O-H stretching mode of water interacting with biomolecule 159 or oxide 160 surface, or confined within carbon nanotubes 161 is consistent with the weakening of the hydrogen-bonded water network in these systems.…”
Section: Intramolecular Vibrationssupporting
confidence: 60%
“…First, it was confirmed that the hydrogen bonding interactions of subsurface hydrous species do not change by heating at 400°C without ion exchange because the temperature was lower than the T g of the sample. The OH stretch peak position is a function of the hydrogen bond strength or the O–H···O distance; it means that the stronger the hydrogen bond is, the larger the OH stretch peak is red‐shifted . After the Na + /K + ‐exchange at 400°C, the ~3550 cm −1 peak of weakly hydrogen bonded species disappears and the ~3160 cm −1 and ~3370 cm −1 are slightly blue‐shifted to ~3200 cm −1 and ~3425 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Attenuated Total Reflection-Infrared (ATR-IR) spectroscopy has been used to monitor the growth of different water layers on a SiO 2 surface. 16 Quasi-elastic neutron scattering experiments have been used to study confined surface water in different materials 11,17 evaluating the vibrational density of states (VDOS), which can be used for the characterisation of the strength of hydrogen bonds, 16 providing information about the mobility of this interfacial water. However, information of local H-bond dynamics (formation and breaking) cannot be obtained with these techniques.…”
Section: Introductionmentioning
confidence: 99%